Outdoor/indoor air quality in primary schools in Lisbon: a preliminary study - Pegas, Priscilla Nascimento (2010)
Simultaneous measurements of outdoor and indoor pollution were performed at three schools in Lisbon. Volatile organic compounds (VOCs), formaldehyde and NO2 were passively monitored over a two-week period. Bacterial and fungal colony-forming units and comfort parameters were also monitored at classrooms and playgrounds. The highest indoor levels of CO2 (2666 µg/m3), NO2 (40.3 µg/m3), VOCs (10.3 µg/m3), formaldehyde (1.03 µg/m3) and bioaerosols (1634 CFU/m3), and some indoor/outdoor ratios greater than unity, suggest that indoor sources and building conditions might have negative effects on air indoors. Increasing ventilation rates and use of low-emission materials would contribute towards improving indoor air quality.